Familiar stories : developing writing skills through contextualized material in a rural school - Acuña Vargas, Yinna Tatiana; Maldonado Higuera, Diana Alejandra; Rodríguez Carreño, Erika Yesenia (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Eng: Rural education lacks contextualized materials for students’ needs. For this reason, this research study portrays a case study in eleventh grades at a rural school of Boyacá. The aim of the study is to analyze the influence of contextualized materials in the development of writing skill through familiar stories workshops. Data was collected by means of a questionnaire, a semistructured interview and students' artifacts. Results showed that the workshops were a possibility to write about one self, family and friends, and the values and moral lessons of their community. Similarly, it portrayed some aspects regarding language awareness such as modeling, grammatical structures and creativity.